Effect of Third-Party Funds on Profitability with Credit Distribution as Moderating Variable - Ida Ayu Gede Utami Dewi, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The economic stability experienced by the banking sector was caused by the Covid-19 pandemic, one of which is in conventional commercial banks. This is inseparable from the sentiment of investors who think that the government has not seriously handled Covid-19, resulting in investors preferring to withdraw their funds rather than depositing their funds in banks which then impact on decreasing bank profitability. The research objectives to be achieved in the form of empirical evidence include the effect of third party funds on profitability with lending as a moderating variable. The study focused on conventional banks listed on the Indonesia Stock Exchange during the period of 2019-2022. Purposive sampling method was used in determining the research sample namely 24 companies with 96 observations. The collection used non-participant observation method by accessing the Indonesia Stock Exchange website. Signaling theory is used to support the results of this study. Data analysis was carried out with Moderated Regression Analysis (MRA) and using the SPSS application. The results of the research show that third party funds have a positive and significant effect on profitability and credit distribution was able to strengthen the effect of third party funds on profitability. The implication of this research is that it is able to support and add knowledge related to the application of signal theory and provide benefits to interested parties, especially companies and investors related to third party funds and credit distribution that can increase profitability.